Assessment of time management practices of small medium sized contractors in project delivery in the Eastern Cape Province, South Africa - Sogaxa, Athenkosi; Simpeh, Eric; Ndihokubwayo, Ruben (University of the Free State, 2021)
The purpose of this article is to assess the effective time-management practices adopted by construction SMEs to enhance successful construction project delivery. A mixed methods approach, consisting of both quantitative and qualitative research methods was adopted. A questionnaire was distributed to Small and Medium Enterprises (SMEs) management team purposively selected from CIDB Grades 1 to 4 registered contractors under the general building category. The quantitative data were analysed, using descriptive statistics. To validate quantitative findings, semi structured interviews were conducted with randomly selected respondents who were part of the survey study where content analysis was adopted. The findings revealed that the most adopted effective time-management practices to enhance the sustainable success rate of construction SMEs in South Africa included progress meeting with consultants to ensure regular monitoring of the work progress, strategic planning to recover time lost, effective management of subcontractors, and allocation of tasks to workers according to their skills and expertise. It should be noted that the quantitative findings were consistent with the qualitative findings, and revealed that effective project planning, periodic progress meetings and labour production contribute to the sustainable success rate of SMEs. The results obtained from this article could be adopted as SMEs’ effective time-management practices to enhance sustainable construction project delivery.
Keywords: Construction projects; Leadership and sustainable success; Project delays; SMEs; Time-management; South Africa